2017
DOI: 10.1007/s00439-017-1847-y
|View full text |Cite
|
Sign up to set email alerts
|

World-wide distributions of lactase persistence alleles and the complex effects of recombination and selection

Abstract: The genetic trait of lactase persistence (LP) is associated with at least five independent functional single nucleotide variants in a regulatory region about 14 kb upstream of the lactase gene [−13910*T (rs4988235), −13907*G (rs41525747), −13915*G (rs41380347), −14009*G (rs869051967) and −14010*C (rs145946881)]. These alleles have been inferred to have spread recently and present-day frequencies have been attributed to positive selection for the ability of adult humans to digest lactose without risk of symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 45 publications
2
74
0
2
Order By: Relevance
“…It was therefore commonly assumed that increased reliance on dairy products from the Early Neolithic would have driven the selection of LP during subsequent millennia. At least five different allelic variants have been identified as causative of LP globally, suggesting convergent evolution (Tishkoff et al 2007;Jones et al 2015;Liebert et al 2017). Initial investigations of the European LCT gene responsible for LP (C-13910 > T; −13910*T allele (rs4988235)) suggested that selection favouring the LP allele may have begun in the Neolithic in conjunction with the spread of agriculture and increased use of domesticated animal species.…”
Section: Lactase Persistence and The Origins Of Milk Consumptionmentioning
confidence: 99%
“…It was therefore commonly assumed that increased reliance on dairy products from the Early Neolithic would have driven the selection of LP during subsequent millennia. At least five different allelic variants have been identified as causative of LP globally, suggesting convergent evolution (Tishkoff et al 2007;Jones et al 2015;Liebert et al 2017). Initial investigations of the European LCT gene responsible for LP (C-13910 > T; −13910*T allele (rs4988235)) suggested that selection favouring the LP allele may have begun in the Neolithic in conjunction with the spread of agriculture and increased use of domesticated animal species.…”
Section: Lactase Persistence and The Origins Of Milk Consumptionmentioning
confidence: 99%
“…Персистенція лактази, що асоціюється з фе-нотипово схожими генотипами С/Т та Т/Т-13910, успадковується як домінуюча менделівська риса, що виникла близько 10 000 років тому серед пле-мен Північної Європи, що займалися скотарством, та зумовила 100-відсотковий рівень експресії лак-тази протягом дорослого життя [12,16,17]. У наш час максимальна частота зустрічальності лактазної персистенції понад 90 % виявляється саме серед на-селення північноєвропейських країн (Скандинавії та Нідерландів), мінімальна зустрічальність алелі Т-13910 менше ніж 50 % представлена серед насе-лення Південної Європи (Італії та Іспанії).…”
Section: вступunclassified
“…Positive selection for LP which allows the dietary consumption of animal milk by adult humans without risk of symptoms of lactose intolerance has been attributed to present day frequencies of these alleles (49-52). Population expansion, migration, allele surfing and cultural/environmental processes may also have influenced the distributions of these alleles (49,52).…”
Section: Lactase Persistence (Lp)mentioning
confidence: 99%